2015
DOI: 10.4067/s0717-95022015000300015
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Ponticulus Posticus, Sella Turcica Bridge and Clinoid Enlargement in Cleft Lip and Palate Peruvian Patients: A Comparative Study with Non-Cleft Patients

Abstract: SUMMARY:The aims of this study were to determine the frequency of the Ponticulus posticus (PP) in the C1 vertebra and the Sella Turcica Bridge (STB) and Clinoid enlargement (CLEN) variants in two samples of Peruvian cleft lip and palate patients (CLP), determine if there are significant differences between sexes and compare the results with two samples of non-cleft controls. The digital images of the lateral cephalometric radiography of 163 and 150 CLP patients were utilized to determine the frequency of PP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
1
12
0
1
Order By: Relevance
“…7 In addition, these anomalies in the cervical vertebrae have been previously reported to be associated with dental anomalies (such as hypodontia, hyperdontia, and palatally displaced canine impaction), 1,2,5,10 maxillofacial malformations, 10 and condylar and vertical craniofacial morphology. 10,24,25 Additionally, the prevalence of PP formation has been reported in patients with craniofacial problems 10 and dental anomalies 1,14 and has also been reported to be associated with certain diseases and syndromes. 7 The results of this study showed that the prevalence of PP formation decreased and PADA increased in patients with BAMLI.s In the absence of any clinical signs or symptoms, STB is considered to be a normal variant, although it is known to be affected by pathological processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 In addition, these anomalies in the cervical vertebrae have been previously reported to be associated with dental anomalies (such as hypodontia, hyperdontia, and palatally displaced canine impaction), 1,2,5,10 maxillofacial malformations, 10 and condylar and vertical craniofacial morphology. 10,24,25 Additionally, the prevalence of PP formation has been reported in patients with craniofacial problems 10 and dental anomalies 1,14 and has also been reported to be associated with certain diseases and syndromes. 7 The results of this study showed that the prevalence of PP formation decreased and PADA increased in patients with BAMLI.s In the absence of any clinical signs or symptoms, STB is considered to be a normal variant, although it is known to be affected by pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 Calcification of the atlanto-occipital ligament, called ''arcuate foramen'' or ''PP,'' was evaluated visually and scored using a standardized method. 3,10,19 It was scored according to the degree of atlantooccipital ligament ossification as no calcification (absent), partial calcification (incomplete), or complete calcification (complete) ( Figure 2). The presence of STB has been previously demonstrated on lateral cephalometric radiographs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with PP, it can be misidentified as a broad posterior arch and the screw can be inserted into the PP. This can cause critical complications [22,24,40].…”
Section: Introductionmentioning
confidence: 99%
“…CLP results in many complications including feeding, speech, hearing and psychological development. Patients with CLP have higher risk than patients in general population for the appearance of cervical vertebral anomalies [7,9,24,25,38]. The purpose of the this study was twofold: to determine of the prevalence and characteristics of PP in patients with CLP, and to compare the findings with patients in general population using cone beam computed tomography (CBCT).…”
Section: Introductionmentioning
confidence: 99%